Vostochnai︠a︡ chastʹ Okhotskago mori︠a︡ otʺ paralleli 50° 45' do paralleli 56° 20' po opisi Gidrograficheskoĭ Ėkspedt︠s︡īi Vostochnago okeana 1914 godʺ / Sostavli︠a︡li i chertili Shturmanʺ d. pl. Ivanovskīĭ - Russia. Glavnoe gidrograficheskoe upravlenīe (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : Морское министерство, Главное гидрографическое управленіе, 1914)
Relief shown by form lines and spot heights. Depth shown by soundings.; Title translation: Eastern part of the Sea of Okhotsk from parallel 50° 45' to parallel 56° 20' according to the survey of the Hydrographic Expedition of the Eastern Ocean 1914.; Greenwich meridian.; Includes table of navigational points.; "Primi︠e︡chanīe: Astronmicheskīe punkty opredi︠e︡leny Podpolkovnikomʺ Davydovimʺ 1914 godu" = Note: Astronomical points plotted by Lieutenant-Colonel Davydov in 1914.; "Masshtabʺ 1/760464 ili 8696 s. (10 milʹ) vʺ di︠u︡ĭmi︠e︡ po paralleli 54° 00' " = Scale 1/760484 or 8696 fathoms (10 miles) in 1 inch on the 54° 00' parallel.; "No. 321." Grayscale; 1:760,464